Helminthes eggs as bio-indicators for soils contamination (Study case: Ghenieri municipality, Jableh_Syria) - حسن بشرى محمد; أمل ابراهيم ديوب (Latakia University Journal -Biological Sciences Series, 2023)
In order to reveal the contamination of soils in Jableh district with wastewater which irrigated with Al-Hwiez Dam lake water, where the sewage is drained from the neighboring villages directly without treating, we relied on the helminthes eggs as one of the most important bio-healthy indicators in this field according to World Health Organization (WHO). soil samples were collected from two sites S1 and S2 in wet and dry seasons from June 2021 to January 2022 in order to processed in the laboratory to determine the presence and concentration of helminthes eggs, types and spread based on specific reference. The microscopic analysis shows contamination with helminthes eggs in the dry seasons with a count of 14-8 egg/4.5g in S1 and S2 respectively, which is higher than the permissible limit according to the standards set by the World Health Organization. According to the approved international classification standards, the morphological and taxonomic study of the recovered eggs showed that it has belong to seven types, namely: Ascaris sp. (36.36%), Ancylostoma duodonela (4.54%), Threadworm (4.54%), Entrobius Vermicularis (18.18%), Fasciola hepatica (4.54%), Taenia sp. (13.63%), Hymenolepis nana (4.54%), and cysts belong to protozoa named Entamoeba histolytica (9.09).The most prevalent eggs were Ascaris sp and Enterobius vermicularis. The study showed the absence of pollution in the rainy seasons, this may be due to the lack of irrigation and the total dependence on rainwater, thus the eggs washed away into the deeper layers of the soil or they are lost with the wastewater. As a result, this study proved that the soil irrigated with Al-Hwiez Dam water in Ghenieri were contaminated with helminth eggs, hence preventive measures should be taken to prevent the spread of intestinal worms’ diseases and other wastewater-transmitted pathogens.